The orphan nuclear receptor RORα and group 3 innate lymphoid cells drive fibrosis in a mouse model of Crohn’s disease - Bernard C. Lo; Matthew J. Gold; Michael R. Hughes; Frann Antignano; Yanet Valdez; Colby Zaph; Kenneth W. Harder; Kelly M. McNagny (2016)
Fibrosis is the result of dysregulated tissue regeneration and is characterized by excessive accumulation of matrix proteins that become detrimental to tissue function. In Crohn's disease, this manifests itself as recurrent gastrointestinal strictures for which there is no effective therapy beyond surgical intervention. Using a model of infection-induced chronic gut inflammation, we show that Rora-deficient mice are protected from fibrosis; infected intestinal tissues display diminished pathology, attenuated collagen deposition, and reduced fibroblast accumulation. Although Rora is best known for its role in group 2 innate lymphoid cell (ILC2) development, we find that Salmonella-induced fibrosis is independent of eosinophils, signal transducer and activator of transcription 6 signaling, and T helper 2 cytokine production, arguing that this process is largely ILC2-independent. Instead, we observe reduced levels of ILC3- and T cell-derived interleukin-17A (IL-17A) and IL-22 in infected gut tissues. Furthermore, using Rorasg/sg /Rag1-/- bone marrow chimeric mice, we show that restoring ILC function is sufficient to reestablish IL-17A and IL-22 production and a profibrotic phenotype. Our results show that RORα (retinoic acid receptor-related orphan receptor α)-dependent ILC3 functions are pivotal in mediating gut fibrosis, and they offer an avenue for therapeutic intervention in Crohn's-like diseases.